Analysis of Sexual Predator Network News Framing in Children in Kompas.com and Joss.co.id Online Media - Habib Firmansyah; Anang Anas Azhar (PT Mattawang Mediatama Solution, 2022)
Sexual harassment against children is becoming increasingly common. Child sexual harassment occurs when a child is persuaded or forced to be used as a sexual object to satisfy one's sexual appetite. Furthermore, as technology advances, sexual harassment can now be perpetrated virtually, via video call connections such as WhatsApp social media. Many circles, including the media crew, have certainly highlighted the news about immorality to the age of this child. The media extensively informs children about sexual harassment through various modes of communication. This study explained that on July 14, 2022, news about the rise of sexual predators in children was conveyed on online media Kompas.com and Joss.co.id. In this study, framing analysis with the Robert Entman model as the analysis model is used so that the content of the news text can be carefully understood by using how to define the problem, diagnose the problem, make moral decisions, and emphasize solutions. Whereas in Kompas.com, the news is clear because it is based on the police narrative, Joss.co.id provides information that is profiteered from other sources and developed in the form of points.